(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2019)
Exhaust system of an automobile consist of three parts such as exhaust manifold, catalytic converter and silencer out of those silencer having very short life span as there is lot of restriction provided to the flow of hot gases due to complex geometry in order to reduce the stress, noise level hence gases staying more time in this section as compare to other two part of exhaust system. There are important areas to be focused during design phase of silencer in order to achieve the uniform distribution of heat over the entire exhaust system which consequently enhanced life of the elements in the exhaust system. The problem recognized for this proposed study is to assess the heat flow during the passage of hot gases and design the passage in such a way that it will minimize the destructive effects of hot-spots and localized thermal stress over the length of the silencer, especially at the front end mating with the exhaust manifold.